Mechanical Unloading Activates FoxO3 to Trigger Bnip3‐Dependent Cardiomyocyte Atrophy. Issue 2 (8th April 2013) - Cao, Dian J.; Jiang, Nan; Blagg, Andrew; Johnstone, Janet L.; Gondalia, Raj; Oh, Misook; Luo, Xiang; Yang, Kai‐Chun; Shelton, John M.; Rothermel, Beverly A.; Gillette, Thomas G.; Dorn, Gerald W.; et al.
Abstract : Background: Mechanical assist device therapy has emerged recently as an important and rapidly expanding therapy in advanced heart failure, triggering in some patients a beneficial reverse remodeling response. However, mechanisms underlying this benefit are unclear. Methods and Results: In a model of mechanical unloading of the left ventricle, we observed progressive myocyte atrophy, autophagy, and robust activation of the transcription factor FoxO3, an established regulator of catabolic processes in other cell types. Evidence for FoxO3 activation was similarly detected in unloaded failing human myocardium. To determine the role of FoxO3 activation in cardiac muscle in vivo, we engineered transgenic mice harboring a cardiomyocyte‐specific constitutively active FoxO3 mutant ( caFoxO3 flox ;α MHC‐Mer‐Cre‐Mer ). Expression of caFoxO3 triggered dramatic and progressive loss of cardiac mass, robust increases in cardiomyocyte autophagy, declines in mitochondrial biomass and function, and early mortality. Whereas increases in cardiomyocyte apoptosis were not apparent, we detected robust increases in Bnip3 (Bcl2/adenovirus E1B 19‐kDa interacting protein 3), an established downstream target of FoxO3. To test the role of Bnip3, we crossed the caFoxO3 flox ;α MHC‐Mer‐Cre‐Mer mice with Bnip3‐null animals. Remarkably, the atrophy and autophagy phenotypes were significantly blunted, yet the early mortality triggered by FoxO3 activation persisted. Rather, declines in cardiac performance were attenuated by proteasome inhibitors. Consistent with involvement of FoxO3‐driven activation of the ubiquitin‐proteasome system, we detected time‐dependent activation of the atrogenes program and sarcomere protein breakdown. Conclusions: In aggregate, these data point to FoxO3, a protein activated by mechanical unloading, as a master regulator that governs both the autophagy‐lysosomal and ubiquitin‐proteasomal pathways to orchestrate cardiac muscle atrophy.